Complementarity and the Excess Burden of Taxation - Corlett, W. J.; Hague, D. C. (Review of Economic Studies, 1953)
W. J. Corlett, D. C. Hague; Complementarity and the Excess Burden of Taxation, The Review of Economic Studies, Volume 21, Issue 1, 1 January 1953, Pages 21